Experimental Investigation on Enhancement of properties in Ablative Liner. (2015) - Gupta, G.S.; Harinath, P.N.V.
Abstract: This paper is on an experimental investigation for evaluating physical, mechanical and thermal properties of an ablative phenolic laminates by manufacturing and testing them. These are manufactured by changing various parameters like with and without reinforcement of micro silica powder of 15 weight percentage of matrix as filler material and the ply orientation of 0° and 35° rosette. These properties of prepared materials have been tabulated and compared as part of analysis. Literature study reveals that S-Glass laminates exhibit better thermal properties than E glass laminates. Hence, this investigation is carried out for enhancement of properties in E-glass laminates.